Multiscale modelling of wall-to-bed heat transfer in fixed beds with non-spherical pellets: From particle-resolved CFD to pseudo-homogenous models. (8th June 2021) - Moghaddam, E.M.; Foumeny, E.A.; Stankiewicz, A.I.; Padding, J.T.
Graphical abstract: Highlights: Study of forced convection heat transfer through packed beds. Discrete pellet effects in narrow tubes with spheres, cylinders and Raschig rings. Significant local deviations from pseudo-homogenous model predictions. Exposition of length-dependence of effective heat transfer parameters. Abstract: We investigate forced convective heat transfer in packings of spheres, cylinders and Raschig rings, made of glass, steel and alumina, in relatively narrow tubes. A detailed comparison is made between resolved pellet-scale, azimuthally-averaged temperature profiles, and 2D-axially-dispersed pseudo-homogenous plug flow (2D-ADPF) predictions. The local temperature deviates significantly from azimuthally-averaged profiles, which in turn deviate from 2D-ADPF predictions. We show that the length dependency of effective heat transfer parameters is caused by thermal (non-)equilibrium between fluid and solid phases along the bed and not related to inadequate insulation of the calming section or the thermocouple's cross or an under-developed velocity and thermal field at the bed inlet. The influence of pellet shape and thermal conductivity and tube-to-pellet diameter ratio on ker and hw are assessed. We conclude that the models of Specchia/Baldi/Gianetto/Sicardi for all flow regimes and of Martin/Nilles for the turbulent regime are recommended for practical use for spherical particles.